2006
DOI: 10.1007/s00234-006-0123-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the utility of diffusion-weighted MRI and apparent diffusion coefficient values in distinguishing central nervous system toxoplasmosis from lymphoma

Abstract: Our study showed that toxoplasmosis exhibits a wide spectrum of diffusion characteristics with ADC ratios which have significant overlap with those of lymphoma. Therefore, in the majority of patients, ADC ratios are not definitive in making the distinction between toxoplasmosis and lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
53
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 12 publications
2
53
0
5
Order By: Relevance
“…These studies identified a variety of brain regions by MRI, including the frontal and parietal lobes amongst other areas of the cerebral cortex, the basal ganglia and the cerebellum (Brightbill et al, 1996;Maeda et al, 2006;Schroeder et al, 2006;Suzuki et al, 2010). In a single study focusing on psychiatric patients, 14 of whom had a diagnosis of schizophrenia, an attempt to amplify parasite DNA using nested PCR from post-mortem tissue from the orbital frontal cortex was unable to detect T. gondii DNA (Conejero-Goldberg et al, 2003).…”
Section: Localization Of T Gondii In the Cnsmentioning
confidence: 99%
“…These studies identified a variety of brain regions by MRI, including the frontal and parietal lobes amongst other areas of the cerebral cortex, the basal ganglia and the cerebellum (Brightbill et al, 1996;Maeda et al, 2006;Schroeder et al, 2006;Suzuki et al, 2010). In a single study focusing on psychiatric patients, 14 of whom had a diagnosis of schizophrenia, an attempt to amplify parasite DNA using nested PCR from post-mortem tissue from the orbital frontal cortex was unable to detect T. gondii DNA (Conejero-Goldberg et al, 2003).…”
Section: Localization Of T Gondii In the Cnsmentioning
confidence: 99%
“…44 Because CNS lymphomas are highly cellular tumors, water diffusion is often restricted, making them appear hyperintense on DWI and hypointense on ADC maps (Figs 4 and 6). 16,40,44,45 This characteristic is shared by acute ischemic stroke, the central necrosis of brain abscesses, the solid portion of high-grade gliomas, and some metastases. 45 However, PCNSL lesions often have more restricted diffusion and lower ADC values than high-grade gliomas and metastases.…”
mentioning
confidence: 99%
“…16,40,44,45 This characteristic is shared by acute ischemic stroke, the central necrosis of brain abscesses, the solid portion of high-grade gliomas, and some metastases. 45 However, PCNSL lesions often have more restricted diffusion and lower ADC values than high-grade gliomas and metastases. 40,46,47 A recent study showed that pretherapeutic ADC tumor measurements within contrast-enhancing regions were predictive of clinical outcome in patients with PCNSL.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cerebral toxoplasmosis and primary cerebral lymphoma are the common causes of ring enhancing lesions of central nervous system in patients with AIDS. However, it is often difficult to distinguish between these two conditions clinically and radiographically 5 .…”
Section: Case Reportmentioning
confidence: 99%